Installation for resonance spectroscopy of radioactive light nuclei - A. G. Artukh; A. G. Foshan; O. D. Grygorenko; S. A. Klygin; G. A. Kononenko; E. I. Koschy; V. E. Kovtun; V. V. Ostashko; Yu. N. Pavlenko; A. N. Ponomarenko; Yu. M. Sereda; A. I. Rundel; et al. (Ядерна фізика та енергетика)
The experimental set-up based on the time-of-flight fragment-separator COMBAS and multi-channel registration system is developed for the studies of exotic light nuclei. Precise correlation method will be used for resonance decay spectroscopy.